Azolla microphylla Bioabsorb as Countermeasures Alternative of Ammonia (NH3-N) In the Cultivation Media - Ahmad Fauzan Saputra; Syafriadiman '; Saberina Hasibuan (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted from March until April 2015 at the Laboratory of Environmental Quality Cultivation of the Faculty of Fisheries and Marine Science University of Riau. The aim of this research to find out the ability of Azolla microphylla absorb ammonia (NH3-N) in reducing the content of ammonia (NH3-N) in the cultivation media. The method used was experimental method and complete randomized design (CAD) with 1 factor 4 treatments and 3 replications. The results of this research that giving of Azolla microphylla with different density give effect to the decrease in ammonia (NH3-N) in the cultivation media. The best density during research was 20 g Azolla microphylla/L of water could reduce ammonia (NH3-N) content in the cultivation media was 0,188 mg/L.